Predicting Outcomes of Rat Vascularized Composite Allotransplants through Quantitative Measurement of Chimerism with PCR-Amplified Short Tandem Repeat. (4th February 2020) - Cheng, Hui-Yun; Huang, Xiao-Ting; Lin, Chih-Fan; AL Deek, Nidal F.; Shih, Ling-Yi; Lin, Cheng-Hung; Wei, Fu-Chan
Abstract : Chimerism has been associated with the induction and maintenance of tolerance to vascularized composite allotransplants (VCA). Although most VCA studies have examined chimerism using flow cytometry, we proposed that precision in the measurement of chimerism may be better approximated when complimentary polymerase chain reaction (PCR) is applied to a specific short tandem repeat (STR). We identified a STR, D10Rat25, which exhibited a ~20 bp difference in length between two rat strains (BN and LEW) often utilized as the donor and recipient in many allotransplantation studies. D10Rat25 was PCR-amplified and quantified with capillary electrophoresis. With pure LEW and BN DNA, a standard curve was constructed to measure chimerism with good linearity. When applied to rat VCA, the relationship between systematic (in peripheral blood) or local (at specific organ/tissues) chimerism to allograft outcomes was noted. We found that peripheral chimerism was elevated by up to ~9% postoperative month 1 (POM 1) but then reduced regardless of the final VCA outcome. However, differences in VCA skin chimerism between early rejection and POM 1 (shown as Δ ChimerismPOM1-ER ) were notable with respect to VCA outcomes. ROC analysis identified the optimum cutoff value as 17.7%. In summary, we have developed a reliable method to quantify the percentage of BN cells/DNA in BN-LEW chimeras. The detection limit was characterized, and the acquired data were comparable with flow cytometry. This method can be applied to solid organ and composite tissue allotransplantation studies.